DRUG-RESISTANT PATTERN AND BIOFILM CHARACTERISTICS OF PSEUDOMONAS AERUGINOSA ISOLATED FROM CLINICAL SAMPLES (Journal of Medical & Health Sciences Review, 2025)
Pseudomonas aeruginosa (P. aeruginosa) is an organism of one health concern. With a high fatality rate, it is an important cause of nosocomial infections in immunocompromised individuals. This study looked into the potential causes of urinary tract infections (UTIs) in hospitalized patients, including P. aeruginosa biofilm formation and drug resistance patterns. In the ongoing study, 105 urine and pus samples from suspected male and female patients were collected from different hospitals, and they were then inoculated on Blood MacConkey and selective Cetrimide Agar for the isolation of P. aeruginosa. Gram's staining was used to identify these isolated strains before biochemical analyses. Disks containing the antibiotics Meropenem (100 mg), Azithromycin (15 mg), Amikacin (30 mg), Gentamicin (30 mg), Aztreonam (30 mg), and Enrofloxacin (5 mg) were used in disc diffusion antimicrobial susceptibility testing. Antibiotic susceptibility was examined using Muller Hinton Agar and findings were obtained by measuring the diameter of the zones surrounding the discs in accordance with CLSI standards. Out of 105 clinical samples, 63 samples were positive for P. aeruginosa. Out of 63 positive, 36 and 27 isolates were positive for females and males, respectively. Overall percentage positivity was 60%. Females showed highest percent positivity, 57.14% while in males it was 42.85%. Patients within the age of 40 60 showed highest percentage positivity. All isolates showed 100% resistance against Azithromycin while Amikacin was resistant in few isolates. Gentamicin, Aztreonam, Meropenem, and Enrofloxacin were found as effective drugs. Positive isolates were further processed for biofilm formation using 96 96-well plate or a micro-titration plate. Out of 63 positive samples, 45 were biofilm-producing, having OD value more than 0.2. Most of them were strong biofilm producers. Our results concluded that P. aeruginosa was a common cause of UTIs and catheter- associated infections in hospitalized patients, and most of these P. aeruginosa strains are biofilm-producing and multidrug-resistant.